Analisis Implementasi Akad Murabahah pada Pembiayaan Kredit Pemilikan Rumah pada Bank Sumut Syariah Kcp Kota Binjai - Aidil Akbar (Pusat Riset dan Inovasi Nasional, 2024)
Bank is a financial institution that acts as an intermediary between individuals or entities who have funds and those who need funds, and the bank also acts as an institution that regulates the flow of payments. This research approach is a qualitative approach which is more descriptive and does not emphasize numbers. Implementing a murabahah agreement for subsidized mortgage financing involves meetings between the company leadership or their representatives, a notary, and prospective customers who apply for financing. During the meeting, the bank conveys provisions such as the bank's profit margin, the amount of principal installments plus the margin that must be paid by the customer, the total installments, details of the objects to be provided by the customer, the installment list, the amount of the down payment, the time period, and other appropriate requirements. with a letter of agreement. Based on the results of research that has been carried out and supported by theories that are the basis for thinking in understanding various problems, as well as the results of discussions that have been presented in this analysis, the conclusions that can be drawn are as follows: First, Bank Sumut Syariah KCP Binjai City implements financing regulations murabahah in Sharia KPR financing with the murabahah bil wakalah scheme.